Factor Structure and Measurement Invariance of Youth Psychopathic Traits Inventory-Child Version in Chinese Children - Ren, Fen; Zhang, Qing-peng; Li, Mingshu; Luo, Jie; Deng, Jiaxin; Zhang, Xintong; Wang, Meng-Cheng (Frontiers in Psychology, 2019)
The primary goal of the present study was to examine the latent factor structure and measurement invariance of the Youth Psychopathic Traits Inventory-Child Version (YPI-CV) in a sample of Chinese children. 299 school children (aged 9–12, 47.3% female) completed the Chinese version of the YPI-CV, and their parents completed a different measure of psychopathic traits, as well as ones for other measures: the Child Problematic Traits Inventory (CPTI), the Strength and Difficulty Questionnaire (SDQ), and the Social Competence – Parent Version (SCPV). Results showed that a bifactor model at item level fit the data best and was invariant across gender. Specifically, the general psychopathy factor influenced the 18 items strongly, suggesting that the YPI-CV is unidimensional rather than multidimensional. Overall, findings suggest that the bifactor structure of the YPI-CV should be used when examining relationships with outcome variables in Chinese children, with a focus on the total score of the YPI-CV, while factor scores should be explained with caution.